Responsibility of Transport Entrepreneurs for the Risk of Damaged Shipped Goods (Study at CV. Maharani Travel) - Hannum, Syarifah; Ramadani, Ramadani (LEGAL BRIEF, 2024)
This research aims to investigate the responsibility of transport entrepreneurs for damaged goods based on Law no. 22 of 2009 concerning Road Traffic and Transportation, with a focus on the CV case study. Maharani Travel. The method used is empirical juridical research by collecting primary data through observation and interviews, as well as secondary data from legal materials and related literature. Based on this research, it can be concluded that transportatiXCZon entrepreneurs, such as CV. Maharani Travel, has clear and firm responsibilities regarding damage to shipped goods as regulated in Article 191 of Law no. 22 of 2009 concerning Road Traffic and Transportation. Transport operators are required to provide compensation for damage to goods that occurs during transportation, unless it can be proven that the damage was not due to their fault or negligence. This research shows that CV. Maharani Travel has implemented quite good claims handling procedures, although there are still several obstacles in the verification and compensation payment process. Therefore, improving administrative efficiency and staff training are essential to ensure consumer satisfaction and compliance with legal requirements.